Penelitian Pelayanan di Perpustakaan dalam Database Google Scholar: Sebuah Narrative Literature Review - Yonna Ananda (Pustabiblia: Journal of Library and Information Science, 2022)
The library as one of the institutions providing information has an obligation to provide excellent service to its user community. The best and quality service is the spearhead of the library and is an important thing to be realized. This study aims to find out service research in libraries in the Google Scholar database which analyzes research themes/topics, research methods, and research results used. The research method uses a qualitative approach through narrative literature review on eight references indexed by the Google Scholar database with a range of publications from 2012 to 2022. The results show that research on library services in the Google Scholar database is a research that has been widely studied in various libraries. According to the theme/topic of research, services in the library. As for the analysis of research methods, library services are widely studied using qualitative and quantitative methods. The nine references analyzed have research results that show that research in a library should pay attention to aspects of service quality dimensions consisting of reliability, responsiveness, assurance, empathy and form in order to meet user needs through measuring the level of satisfaction, so that an organization must be able to improve improvements. in the quality of library services. Quality services have helped the purpose of the library in improving the image of the library and meeting the expectations and needs of users.